Breast cancer histology and hormonal status characterization in Libyan patients; a sample from middle region (Sirte Journal of Medical Sciences, 2022)
Background: Breast cancer, has increased in developed and developing countries among females, and in Libya, often diagnosed at advanced stage. This study conducted to evaluate histological features and hormonal status of breast carcinoma in Libyan females. Materials and Methods: This retrospective study was performed at Sirte Oncology Centre, Sirte, Libya. Demographic characteristics, such as age, sex, marital status recorded. Histopathology examination provided the histologic type, grade, tumor size, stage, lymph node status, site of metastasis and hormonal status. Data were obtained and analyzed using SPSS software version18.0.Results: A total of 74 breast cancer patients of which 72 (97.3%) were females and 2 (2.7%) were males. Majority of the cases occurred in the 5th decades. Invasive ductal carcinoma of no specific type was the most commonly diagnosed type of breast carcinoma accounting 95.9% of total cases, invasive lobular, ductal and lobular carcinoma and malignant phylloides were the second most common types. Majority of cases (57.4%) diagnosed with grade III tumors and 60 % of cases were found at advanced invasive and metastatic stage of breast cancer. Most of cases showed positive hormonal receptors (both ER and PR positive) (67.2%) while triple negative (ER, PR, and Her2Neu negative) cases were found to be the rarest group (1.6%). Conclusion: Invasive ductal carcinoma was the most common histological type of breast cancer in Libyan patients, commonly diagnosed with a higher grade and at advanced stage. As hormonal status carries a hope of benefit from hormonal treatment, so our study places the significance of early detection, histo-pathological informations and hormonal status in an appropriate treatment strategy.
Keywords: Breast carcinoma; invasive ductal carcinoma; hormonal status